Thermal Environment and Psychological Well-Being in Low Prices Housing on Warm and Dry Climate - Espinoza Gallego , Noelia Beatriz (Consorcio de Universidades Mexicanas A.C., 2014)
The objective of this study was to determine the effect of the thermal environment of social housing in the psychological well-being of its residents in two seasons (summer and winter), starting to develop and test two structural equation models.The study was conducted in Hermosillo, Sonora, Mexico, a city located in a semi desert, arid and warm climate. The study of meaning and environmental perception involves two aspects included in this job: One is an objective or physical component, and the second one is a subjective component. The first one was indicated by features of the physical context, which affect the meaning attributed to it, and the second, one by a set of internal representations about the environment including the emotions produced experienced by people. An evaluation was conducted considering the above-mentioned components. The first one was evaluated using tools that assessed the housing thermal conditions, and the second one through an instrument adapted and validated for this study with the purpose of assessing aspects related to psychological well-being. The main finding we mention that the obtained models showed that the thermal environment inside the housing affects the psychological well-being of people only in the summer season as a negative and significant relationship between the two factors is observed and not this relationship is presented significant in the model developed for the winter.